2021
DOI: 10.1177/14673584211054602
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the psychological contract of travel agency employees during the COVID-19 pandemic: The moderating role of mindfulness

Abstract: This study investigates the influence of psychological contract breach (PCB) on work-related attitudes and behaviors (i.e., organizational cynicism, workplace incivility and work alienation) and employees’ emotional exhaustion. It also examines the direct association between these attitudes and behaviors and emotional exhaustion as well as investigating how mindfulness moderates these associations. Based on a quantitative approach, data were collected from 437 employees of Egyptian travel agencies. The PLS-SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…These results are in line with the findings of previous studies (e.g., Choo et al, 2019 ; Khoury et al, 2013 ; Verplanken & Fisher, 2014 ), which showed that mindfulness is an effective tool in reducing physiological symptoms related to anxiety and levels of self-perceived stress. These results also support the findings of some prior studies (e.g., Irum et al, 2020 ; Mekawy et al, 2021 ) indicating that a low level of mindfulness can increase depression and anxiety, resulting in a high level of emotional exhaustion. To be more specific, through the practice of mindfulness, cortical plasticity is enhanced (Yang et al, 2019 ), resulting in reduced anxiety and stress (Choo et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in line with the findings of previous studies (e.g., Choo et al, 2019 ; Khoury et al, 2013 ; Verplanken & Fisher, 2014 ), which showed that mindfulness is an effective tool in reducing physiological symptoms related to anxiety and levels of self-perceived stress. These results also support the findings of some prior studies (e.g., Irum et al, 2020 ; Mekawy et al, 2021 ) indicating that a low level of mindfulness can increase depression and anxiety, resulting in a high level of emotional exhaustion. To be more specific, through the practice of mindfulness, cortical plasticity is enhanced (Yang et al, 2019 ), resulting in reduced anxiety and stress (Choo et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…For example, mindfulness helps reduce negative emotions and rumination, depressive symptoms, anxiety, and burnout (Ge et al, 2019 ; Mugrabi et al, 2020 ; Shapiro et al, 2008 ; Vu et al, 2022 ). Moreover, mindfulness can improve health and emotional tolerance (Irum et al, 2020 ; Kabat-Zinn, 2005 ; Mekawy et al, 2021 ; Parto & Besharat, 2011 ). In the context of COVID-19, Antonova et al ( 2021 ) have indicated that the mechanism of mindfulness had an important beneficial application in dealing with anxiety and promoting well-being.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Workplace behavior and role ambiguity/work-associated stressors were seen to have a considerably high effect on TOI (Park and Min, 2020). The COVID-19 pandemic struck the tourism industry resulting in various detrimental circumstances, including beaching of psychological contract, leading to high levels of negative work behavior and emotional exhaustion (Mekawy et al, 2021). This could force employees to leave their jobs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…PLS-SEM is an analytical method that is frequently utilized in a variety of studies, including tourist research. It is an appropriate method to evaluate intricate structural models that have several variables with direct and indirect paths (Mekawy et al, 2022).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%